Mitigation of Salinity Stress on Vetiver Grass (Vetiveria zizanioides) through Application of Micrococcus yunnanensis and Indole-3-Acetic Acid - Negar Mosallanejad; Mehdi Zarei; Reza Ghasemi-Fasaei; Amir Ghaffar Shahriari; Afsaneh Mohkami; Imre Majláth; Ramesh R. Vetukuri (Agronomy, 2024)
Salinity represents an ever-challenging problem of agriculture in arid and semi-arid regions. This problem is considered a key limiting factor of agricultural production in the countries of Southwest Asia. In recent years, the use of alternative methods of chemical fertilizers has emerged as a promising approach to mitigate the negative effects of salinity on crop yield. In this research, the effect of Micrococcus yunnanensis and indole-3-acetic (IAA) acid on the growth and chemical composition of Vetiver grass (Vetiveria zizanioides) under salt stress has been investigated. Based on the results, application of IAA, M. yunnanensis and their interaction significantly increased the average plant growth, fresh and dry weight of aerial parts and root dry weight. Considering chemical properties of the plant, interaction between IAA and M. yunnanensis significantly increased shoot phosphorus, potassium and sodium absorption. Proline content, catalase, superoxide dismutase and peroxidase activity were significantly influenced by application of IAA, M. yunnanensis and their interaction. Follow-up experiments after vetiver harvest showed that IAA and M. yunnanensis treatments improved soil microbial biomass and respiration. In total, plant biomass improved by 34% and the activities of catalase, superoxide dismutase and peroxidase enzymes decreased by −20.61, −4.70 and −8.00%, respectively, which shows that the stress pressure on the plant has decreased. This study reinforces the previous literature on the positive effects of biological treatments to improve plant performance by providing new evidence of the positive effects of IAA and M. yunnanensis on mitigating the negative effects of salinity.